SOCIO-ECONOMIC FACTORS RELATED TO REARING FEMALE DOGS IN INDIA: RELATION TO THE DEVELOPMENT OF CEH-PYOMETRA - PATRA, M K; SINGH, U K; K S, JISNA; T R, RAJIN; DE, U K; SAXENA, A C; KRISHNASWAMY, NARAYANAN; KUMAR, H (The Indian Journal of Animal Reproduction, 2021)
Pyometra is one of the major reproductive problems in intact bitches at middle to advance age. Present study describes the impact of breed, age, management and breeding practices of dog in the prevalence of CEH-pyometra in the bitch. A questionnaire based questionnaire based interview was conducted on 93 pet owners who have visited the Gynaecology unit of Referral Veterinary Polyclinic, Indian Veterinary Research Institute, Izatnagar. The point prevalence of pyometra was 34.4%. About 76.3% responders mentioned the purpose of keeping pets as a part of hobby or special interest to the dog, however, only 11.8% owners were keeping dog for safety at their home. Labrador was the most preferred breed among the responder (34.4%), followed by Pomeranian (11.8%). Most of the owners (81.7%) maintained single dog and about 50.5% owners did not breed the female, whereas 24.7% maintained the female without breeding after a single whelping. The awareness about use of hormones in controlling estrus and termination of pregnancy was negligible, only 3.2% owners have used hormones as contraceptive. Most of them preferred to consult veterinarian at Government hospitals than private veterinary dispensary. Although, majority of responders used disinfectant for cleaning the area used by their pet, around 15% responders did not use any disinfectant. Thus, more preference towards single or no whelping until middle to advance age and lack of awareness on regular breeding and proper use of antiseptic and disinfectant for cleaning of pet cages or houses could be the major risk factors for development of CEH-pyometra in the bitch.